Efeito protetor do chá verde (Camellia sinensis) contra a ação genotóxica da doxorrubicina, em células somáticas de Drosophila melanogaster - Araújo, Bethânia Cristhine de (2008)
The green tea is considered a functional food with antioxidant activity, and this delays the process of old age and helps in the prevention of chronicle and degenerative diseases, such as cancer and heart affections. Of catechins, present in green tea, may is extremely important in the inactivation of free radicals, which provoke damages to the DNA molecules and to the cell membranes prevent the cytotoxicity induced by the oxidative stress in different tissues, by actuating in the process of chemoprevention. In this study two crosses, ST and HB aimed at evaluating the protective effects of green tea in three different concentrations (25, 50 e 75mg/mL), combined with the antitumor agent, doxorrubicin (DXR), of the genotoxic action; by the of wing spot test (SMART) of Drosophila melanogaster. The results obtained demonstrated that in MH descendants there was not a statistically significant increase in the frequencies of spots, in the individuals treated with green tea, in standard cross (ST) as well as in the high bioactivation cross (HB - characterized by a high constitutive level of cytochrome P450) . However we could observe a statistically significant decrease in the sum of mutant spots, in MH descendants of both crossings (ST and HB), in all concentrations of green tea associated to DXR. These results suggest that green tea does not present genotoxic effect, but presents protective affect against the mutagenic and recombinagenic action of DXR in the somatic cells of D. melanogaster, in the experimental concentrations used in this study.